Identification of an Endoglin Variant Associated With HCV-Related Liver Fibrosis Progression by Next-Generation Sequencing - About, Frédégonde; Bibert, Stéphanie; Jouanguy, Emmanuelle; Nalpas, Bertrand; Lorenzo, Lazaro; Rattina, Vimel; Zarhrate, Mohammed; Hanein, Sylvain; Munteanu, Mona; Müllhaupt, Beat; Semela, David; Semmo, Nasser; et al. (Frontiers in Genetics, 2019)
Despite the astonishing progress in treating chronic hepatitis C virus (HCV) infection with direct-acting antiviral agents, liver fibrosis remains a major health concern in HCV infected patients, in particular due to the treatment cost and insufficient HCV screening in many countries. Only a fraction of patients with chronic HCV infection develop liver fibrosis. While there is evidence that host genetic factors are involved in the development of liver fibrosis, the common variants identified so far, in particular by genome-wide association studies, were found to have limited effects. Here, we conducted an exome association study in 88 highly selected HCV-infected patients with and without fibrosis. A strategy focusing on TGF-β pathway genes revealed an enrichment in rare variants of the endoglin gene (ENG) in fibrosis patients. Replication studies in additional cohorts (617 patients) identified one specific ENG variant, Thr5Met, with an overall odds ratio for fibrosis development in carriers of 3.04 (1.39-6.69). Our results suggest that endoglin, a key player in TGF-β signaling, is involved in HCV-related liver fibrogenesis.